2014
DOI: 10.3168/jds.2014-8169
|View full text |Cite
|
Sign up to set email alerts
|

Chewing, rumen pool characteristics, and lactation performance of dairy cows fed 2 concentrations of a corn wet-milling coproduct with different forage sources

Abstract: We used a novel corn wet-milling coproduct [CMP; approximately 70% dry matter, 28% crude protein, 36% neutral detergent fiber (NDF), and 18% nonstructural carbohydrates] in diets formulated to contain 18.4% forage NDF, 17.4% crude protein, 20.2% starch, and 3.7% sugar. Six primiparous, rumen-cannulated Jersey cows were assigned to a 6 × 6 Latin square design with a 2 × 3 factorial arrangement of treatments. Diets were formulated to contain 20 and 30% CMP with 3 forage sources [corn silage (CS) and 40.5% NDF, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
(52 reference statements)
1
2
0
Order By: Relevance
“…In the current study, our results on ruminal pH were not different between the SO and SS groups, which ranged between 5.59 and 5.38. This was consistent with previous studies, which reported that rumen pH was not changed by ber source [23,24]. As for the low pH value in calf rumen, it may be attributed to the fact that the absorption rate of VFA by the rumen epithelium of calves was lower than the production rate of VFA.…”
Section: Discussionsupporting
confidence: 92%
“…In the current study, our results on ruminal pH were not different between the SO and SS groups, which ranged between 5.59 and 5.38. This was consistent with previous studies, which reported that rumen pH was not changed by ber source [23,24]. As for the low pH value in calf rumen, it may be attributed to the fact that the absorption rate of VFA by the rumen epithelium of calves was lower than the production rate of VFA.…”
Section: Discussionsupporting
confidence: 92%
“…It is important to differentiate between a depressed appetite and the inability to prehend food due to other causes (e.g., pain, paralysis). Dairy cattle with ad lib access to feed eat for 5.0 ± 2.5 h per day in a feedlot system (dependent on tie or free-stall system, diet, and physiological status of the dairy cattle individual of interest) and 7.0 ± 3.5 h in pasture-based systems (dependent on sward characteristics such as lush pasture or thorny bushes) in several eating bouts (4–20) [ 9 , 14 , 16 , 50 , 54 , 60 , 63 , 65 , 66 , 69 , 72 , 73 , 77 , 80 , 89 , 91 , 97 , 101 , 114 , 115 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 ]. Dairy cattle on pasture show a distinct diurnal feeding behavior [ 9 , 40 , 61 , 82 , 87 , 103 , 108 , ...…”
Section: Assessment Of Feedingmentioning
confidence: 99%
“…The maximum total chewing time has been estimated at 16 h per day [ 101 ]. Normal, healthy cattle ruminate for 7.0 ± 3.5 h a day in several rumination bouts (10 to 20) [ 9 , 14 , 21 , 48 , 54 , 59 , 63 , 66 , 69 , 72 , 76 , 77 , 89 , 114 , 117 , 119 , 121 , 122 , 123 , 124 , 126 , 127 , 128 , 129 , 130 , 132 , 133 , 134 , 135 , 139 , 142 , 143 , 159 , 162 , 163 , 164 , 169 , 173 , 176 , 177 ]. Each bout lasts 10–60 min (range 0.5–120.0 min) [ 76 , 101 ].…”
Section: Assessment Of Feedingmentioning
confidence: 99%